Will using blended learning, peer instruction, pair programming and live coding better facilitate teaching programming and data manipulation? - Jung Kjær, Lene (Improving University Science Teaching and Learning, 2023)
Programming can be challenging to teach, as learning how to program is often perceived as difficult by students (Sharma et al., 2020). Programming is a relatively new discipline and the learning curve is rather steep causing some people to give up before they gain a working understanding on how to code. Teachers of computer programming are faced with a difficult challenge, as there are no perfect and finite guidelines for how to best teach computer programming (Brown & Wilson, 2018; Sharma et al., 2020). However, as learning to code is a very hands-on process, a handson approach may be more effective than a more passive approach (Wilson, 2019).